A 3-Mb Contig from D11S987 to MLK3, a Gene-Rich Region in 11q13 - Smith, Carissa M.; Ma, Nancy S.; Nowak, Norma J.; Shows, Thomas B.; Gerhard, Daniela S.

(untitled) (Genome Research, 1997)
We have combined genetic, radiation-reduced somatic cell hybrid (RRH), fluorescent in situ hybridization (FISH), and physical mapping methods to generate a contig of overlapping YAC, PAC, and cosmid clones corresponding to >3 continuous Mb in 11q13. A total of 15 STSs [7 genes (GSTP1, ACTN, PC, MLK3, FRA1, SEA, HNP36), 4 polymorphic loci (D11S807, D11S987, GSTP1, D11S913), 3 ESTs (D11S1956E, D11S951E, and WI-12191), and 1 anonymous STS (D11S703)], mapping to three independent RRH segregation groups, identified 26 YAC, 7 PAC, and 16 cosmid clones from the CGM, Roswell Park, CEPH Mark I, and CEPH MegaYAC YAC libraries, a 5 genome equivalent PAC library, and a chromosome 11-specific cosmid library. Thirty-six Alu–PCR products derived from 10 anonymous bacteriophage λ clones, a cosmid containing the polymorphic markerD11S460, or STS-positive YAC or cosmid clones were identified and used to screen selected libraries by hybridization, resulting in the identification of 19 additional clones. The integrity and relative position of a subset of clones was confirmed by FISH and were found to be consistent with the physical and RRH mapping results. The combination of STS and Alu–PCR-based approaches has proven to be successful in attaining contiguous cloned coverage in this very GC-rich region, thereby establishing for the first time the absolute order and distance between the markers: CEN–MLK3–(D11S1956E/D11S951E/WI-12191)–FRA1–D11S460–SEA–HNP36/D11S913–ACTN–PCD11S703–GSTP1–D11S987–TEL.[On-line supplementary material concerning screening materials and clones referred to in the text as Table 1 is available athttp://genome.wustl.edu/gerhard/gerhard.html or http://www.cshl.org/gr. The sequence data described in this paper have been submitted to the GenBank data library under accession no. AF009361.]